(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Social innovation, the process of developing and implementing new, effective solutions to solve social or environmental issues came from national policies, governmental or non-governmental entities settle the social issues to meet the social current needs better than it has been done before. As social innovation have to meet the long term impact at large scale through non-profit endeavors and the business community, it also open to address the society’s challenges too. Considering the need for social innovation for a developing country like India, the topic “Social Innovation and Youth in India” analysis the how social innovation can serve the society through youths (one of the most important assets for India).